2022
DOI: 10.1287/msom.2021.1070
|View full text |Cite
|
Sign up to set email alerts
|

Seeing the Bigger Picture? Ramping up Production with the Use of Augmented Reality

Abstract: Problem definition: Firms increasingly use augmented reality (AR) devices to improve their production ramp-up processes. These devices appear useful, yet little is known about their broader impact on worker productivity and behavior. Academic/practical relevance: Efficient production ramp-ups are particularly important when product life cycles are short. An ongoing debate among academics and practitioners pertains to how Industry 4.0, and AR devices in particular, can accelerate the ramp-up. The current study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…However, the first important finding regarding the inclusion of IoT technologies is that when they are operated as stand-alone, without lean support, they negatively impact job engagement and problem-solving. This is consistent with the findings of Letmathe and R€ oßler (2022), Roscoe et al (2019) and Wuttke et al (2022), which showed that workers who use these technologies for work have difficulties remembering information and turning it into learning. However, the results also show that when IoT technologies are integrated with Lean practices rather than operating alone, this combination significantly moderates job engagement and systematic problem-solving.…”
Section: Systematic Problem-solvingsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the first important finding regarding the inclusion of IoT technologies is that when they are operated as stand-alone, without lean support, they negatively impact job engagement and problem-solving. This is consistent with the findings of Letmathe and R€ oßler (2022), Roscoe et al (2019) and Wuttke et al (2022), which showed that workers who use these technologies for work have difficulties remembering information and turning it into learning. However, the results also show that when IoT technologies are integrated with Lean practices rather than operating alone, this combination significantly moderates job engagement and systematic problem-solving.…”
Section: Systematic Problem-solvingsupporting
confidence: 91%
“…This is consistent with the findings of Letmathe and Rößler (2022), Roscoe et al . (2019) and Wuttke et al . (2022), which showed that workers who use these technologies for work have difficulties remembering information and turning it into learning.…”
Section: An Overview Of the Studies Of The Special Issuementioning
confidence: 97%
“…pick support tools, with task complexity as a moderator). This is supported by a recent experiment by Wuttke et al. (2022), who showed that augmented reality (AR) tools can enhance learning significantly.…”
Section: Discussionmentioning
confidence: 74%
“…Another individual measure that might be adopted is to provide tools that aid the workers during job completion. One such tool is AR, which seems to affect the learning rate (at the cost of short-lasting, superficial learning, Wuttke et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, companies invest significant time and energy to ensure that knowledge is transferred and retained successfully during a move. Practices adopted in the industry include, for example, creating standard operating procedures, structured codification (Kotlarsky et al ., 2014), the use of augmented reality devices (Wuttke et al ., 2022) or the “copy exactly” approach (McDonald, 1998). These practices create templates that allow firms to capture existing knowledge and then apply this knowledge to the new site to speed up the learning process during the production ramp-up.…”
Section: Introductionmentioning
confidence: 99%